Speed reading for dummies - Sutz, Richard; Weverka, Peter (Hoboken, NJ : Wiley Pub., 2009)
Covering the latest speed-reading techniques and tips, this guide will help people read quickly and successfully no matter what they read.
Part 1. Introducing speed reading. Of course you can speed read! ; It's all about breaking bad reading habits ; Understanding the mechanics of speed reading ; Introducing speed-reading fundamentals -- Part 2. Focusing on the fundamentals. Establishing your reading rate ; Taking in more than one word at a time : reading in clumps ; Getting the gist from word groups -- Part 3. Advancing your speed-reading skills. Building your speed-reading momentum ; Exercising your ability to read more in even less time ; Other reading strategies to supplement your speed reading ; Taking advantage of writing structure to read more quickly -- Part 4. Improving your comprehension. Expanding your vocabulary to become a better speed-reader ; Applying speed reading to various reading tasks -- Part 5. The part of tens. Ten quick techniques to improve your reading speed ; Ten exercises for keeping your eyes speed-reading ready ; Ten tips for making your speed-reading skills permanent -- Part 6. Appendixes. Appendix A, Uncovering the prime words ; Appendix B, Your speed-reading progress worksheet.
Includes index.
Faculty
Keywords: Speed reading